Coagulation Profile in Perinatal Asphyxia - Dr Srinivasa Murthy Doreswamy; Dr Vani Krishnamurthy (Pediatric Review: International Journal of Pediatric Research, 2015)
Introduction: Perinatal asphyxia is a common problem with devastating consequences in neonatal practice. Bleeding due to coagulation abnormality is very common and is potentially treatable. Various mechanisms including liver dysfunction, unresponsiveness to Vitamin K and consumption of coagulation factors all have been implicated in severe bleeding in asphyxiated neonates. The magnitude of this problem and therapeutic window if present has not been well studied.Methods: this was a prospective study undertaken in a tertiary care centre. 20 babies were recruited for the study. Asphyxia was defined on pragmatic basis of Apgar score and need for resuscitation followed by clinical course. The blood sample was collected in citrated tubes and analysed for coagulation parameters.Results: 55% of our subjects were having deranged coagulation. APTT was the commonest deranged parameters in all our subjects (11/20). PT was deranged in only 2 of 20 patients. Patients who had deranged coagulation had poor outcomes. Coagulation abnormalities within first 24 hours had a positive predictive value of 18% and negative predictive value of 100% with respect to later bleeding.Conclusion: Deranged coagulation is very common in asphyxiated neonates and is associated with poor outcome.